Study on influencing factors of microbial induced carbonate precipitation in a cross fracture network. Issue 7 (October 2021) - Guo, L; Liao, M; Peng, Y; Liu, F; He, X; Guo, H; Wang, B
Abstract: Microbial mineralized precipitation has been widely used in anti-seepage of fractured rock mass due to its environmentally friendly characteristics. The mineralization and sedimentation of the fractured network with vertical and horizontal crosscutting directly affect the anti-seepage of its engineering. Based on the Navier-Stokes equations, solute transport equations, biochemical reaction equations, solution transport, and carbonate precipitation law of the cross fracture networks in rock mass were analyzed. The influence of the Reynolds number (Re) at the inlet, Angle (α) between principal fractures and branch fractures, and fracture aperture degree on the calcium carbonate precipitation were investigated. The results showed that under the condition of two branch fractures, when 1≤Re≤5, there is a weak nonlinear relationship between flow rate (Ra) and Re, where Ra is unaffected by the change of α. When 5<Re≤100, the nonlinear relationship between Re and Ra increased sharply. For 45°≤α≤180°, Ra and α showed a positive correlation due to the gradual increase of the inertial force. After Re>100, Ra gradually became steady. The influence of Re and Ra on the calcium carbonate precipitation in the cross fracture is mainly realized by controlling the change of Ra. For the α=45° model, when Re=1, the amount of calcium carbonate precipitation in the two branch fractures is approximately the same. When Re=100, the maximum concentration of calcium carbonate in the left branch fracture was 60.2 mol/m 3, significantly higher than that in the right branch fracture. The research results provide a useful reference in MICP seepage prevention technology applications in a fractured rock mass.